Strategies of Integrated Tourism for Sustainable Rural Development – A Case Study in Bogaiya Village, Sylhet, Bangladesh - Moon, Farha; Saha, Kawshik (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Across rural Bangladesh there is considerable untapped potential for sustainable development that awaits strategic interventions to activate it properly. Such areas are severely affected by economic challenges, including poverty and geographic isolation. Consequently, local economies struggle to progress and meet the sustainability requirements for achieving social equity. This study was conducted in Bogaiya Village of Gowainghat Upazila, Sylhet, Bangladesh, to determine the possibility of implementing integrated tourism as a pathway to sustainable rural development. Through a mixed-methods approach based on both primary participatory research and secondary literature review, this study looks at the socioeconomic setup of the remote Bogaiya Village in relation to tourism. The results indicate considerable possibilities for social and economic advancement, improving neighbourhood well-being through tourism growth. In particular, the study identifies key areas like local crafts, cultural heritage sites, and eco-tourism activities that can drive economic growth by capitalising on tourist interest in the region’s natural beauty and culture. At the same time, the research indicates that community participation and engagement are crucial in making tourism development work for people and stimulating citizenship and social equity. This paper aims to provide strategic directions in facilitating sustainable rural tourism development, which can offer an archetype for similar types of landscapes in Bangladesh. The guidelines incorporate helpful insights for policymakers, community leaders, and development practitioners to provide an ecosystem that facilitates tourism investment while fostering stakeholder partnership. Ultimately, the study aligns with the 2030 Sustainable Development Goals and suggests how integrated tourism can help rural development, poverty alleviation, and environmental conservation.